Fazoda tekislikka va to`g`ri chiziqqa nisbatan simmetrik almashtirishlarning umumlashgan formulalari - Abjalilov, S.X. (SCIENCE and SOCIETY, 2020)
The article contains information about the analytical expression of actions in space. It presents the methodology of finding the generalized formula of symmetry in straight line and plane in space.